Longitudinal Structural MRI in Neurologically Healthy Adults. Issue 5 (29th May 2020) - Gregory, Sarah; Lohse, Keith R.; Johnson, Eileanoir B.; Leavitt, Blair R.; Durr, Alexandra; Roos, Raymund A.C.; Rees, Geraint; Tabrizi, Sarah J.; Scahill, Rachael I.; Orth, Michael
Abstract : Background: Structural brain MRI measures are frequently examined in both healthy and clinical groups, so an understanding of how these measures vary over time is desirable. Purpose: To test the stability of structural brain MRI measures over time. Population: In all, 112 healthy volunteers across four sites. Study Type: Retrospective analysis of prospectively acquired data. Field Strength/Sequence: 3 T, magnetization prepared – rapid gradient echo, and single‐shell diffusion sequence. Assessment: Diffusion, cortical thickness, and volume data from the sensorimotor network were assessed for stability over time across 3 years. Two sites used a Siemens MRI scanner, two sites a Philips scanner. Statistical Tests: The stability of structural measures across timepoints was assessed using intraclass correlation coefficients (ICC) for absolute agreement, cutoff ≥0.80, indicating high reliability. Mixed‐factorial analysis of variance (ANOVA) was used to examine between‐site and between‐scanner type differences in individuals over time. Results: All cortical thickness and gray matter volume measures in the sensorimotor network, plus all diffusivity measures (fractional anisotropy plus mean, axial and radial diffusivities) for primary and premotor cortices, primary somatosensory thalamic connections, and the cortico‐spinal tract met ICC. The majority of measures differed significantly between scanners, with a trend for sites using Siemens scanners to produce larger values for connectivity, cortical thickness, and volume measures than sites using Philips scanners. Data Conclusion: Levels of reliability over time for all tested structural MRI measures were generally high, indicating that any differences between measurements over time likely reflect underlying biological differences rather than inherent methodological variability. Level of Evidence: 4. Technical Efficacy Stage: 1.